2003
DOI: 10.1007/s00435-003-0076-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of diurnal filter feeding by a novel gill structure in Amblypharyngodon melettinus (Teleostei, Cyprinidae)

Abstract: A unique gill structure, apparently associated with filter feeding on phytoplankton and suspended microdetritus, has been found in Amblypharyngodon melettinus, an abundant small Cyprinidae of Sri Lanka. The gill lamellae, the site of gas exchange, are bordered by a double row of fine appendices which are spread over the interlamellar gaps during daytime, but folded up at night. A respiratory function of the appendices can be excluded. The changing position of appendices correlates with the diurnal pattern of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…During the present study, it was evident that fine detritus (FDT) was a major food source for many fish species in YO‐DZ, especially during LDR. Hofer, Salvenmoser, and Schiemer, () have shown that A. melettinus exhibited a unique mechanism for filter feeding phytoplankton and FDT through a double row of fine appendices which were spread over the interlamellar gaps during daytime, but folded up at night. However, in EO‐WZ, where leaf litter decomposition rate is low (Walpola, Leichtfried, Amarasinghe, & Füreder, ), detritus was not a common source of food for fish so that this stream does not support high densities of detritivorous fish species.…”
Section: Discussionmentioning
confidence: 99%
“…During the present study, it was evident that fine detritus (FDT) was a major food source for many fish species in YO‐DZ, especially during LDR. Hofer, Salvenmoser, and Schiemer, () have shown that A. melettinus exhibited a unique mechanism for filter feeding phytoplankton and FDT through a double row of fine appendices which were spread over the interlamellar gaps during daytime, but folded up at night. However, in EO‐WZ, where leaf litter decomposition rate is low (Walpola, Leichtfried, Amarasinghe, & Füreder, ), detritus was not a common source of food for fish so that this stream does not support high densities of detritivorous fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, Hofer et al . () discussed a type of feeding mechanism in Amblypharyngodon melettinus (Valenciennes 1844) where the unique gill structure of the fish plays a significant role in filter feeding. To fish with such a feeding strategy, size selection at the ingestion level could be an added advantage, as evident from this study.…”
Section: Discussionmentioning
confidence: 99%
“…In all the Sri Lankan reservoirs studied, Amblypharyngodon melettinus, a seston-filtering cyprinid feeding with a remarkable diurnal cycle in migration and filter-feeding (Hofer et al 2003 ), shows a dominance of over 50% of the biomass and even greater proportion of biological productivity (Pet et al 1996 ). Ubolratana reservoir is dominated numerically by the zooplanktivorous Thai river sprat ( Clupeichthyes aesarnensis ), a minute gobiid Gobiopterus chuno and many small-sized cyprinids (see Schiemer 2008 ).…”
Section: Understanding Aquatic Ecosystems As a Prerequisite For A Sus...mentioning
confidence: 99%
“…2 : arrow 2a) by enhancing nutrient release from the bottom strata through faeces production and enhanced bacterial activity. Small-sized cyprinid species like A. melettinus tend to shift the phytoplankton community to cyanobacteria and, in turn, stimulate primary production and eutrophication (Hofer et al 2003 ).…”
Section: Understanding Aquatic Ecosystems As a Prerequisite For A Sus...mentioning
confidence: 99%